Aromatic hydroxylation at a non-heme iron center: insights into the nature of metal-based oxidant. - Makhlynets, Olga. (2017)
Abstract: Mechanism of substrate oxidations with hydrogen peroxide in the presence of highly reactive biomimetic aminopyridine iron compex, [FeIIBPMEN(CH3CN)2](ClO4)2 (1), is elucidated. 1 has been shown to be an excellent catalyst for epoxidation and functional group- directed aromatic hydroxylation using H2O2, although its mechanism of action remains largely unknown.[1, 2] Efficient intermolecular hydroxylation of unfunctionalized benzene and substituted benzenes with H2O2 in the presence of 1 is found in the present work. Detailed mechanistic studies of the formation of iron(III) phenolate products are reported. We have identified, generated in high yield, and experimentally characterized the key FeIII(OOH) intermediate (λmax = 560 nm, rhombic EPR signal with g = 2.21, 2.14, 1.96) formed by 1 and H2O2. Stopped-flow kinetic studies showed that FeIII(OOH) does not directly hydroxylate the aromatic rings, but undergoes rate-limiting self-decomposition producing transient reactive oxidant. The reactive species formation is facilitated by acid-assisted cleavage of the O-O bond in the iron-hydroperoxide intermediate. Acid-assisted benzene hydroxylation with 1 and a mechanistic probe, MPPH, correlates with O-O bond heterolysis. Independently generated FeIV=O species, which may originate from O-O bond homolysis in FeIII(OOH), proved to be inactive toward aromatic substrates. The reactive oxidant derived from 1, exchanges its oxygen atom with water, and electrophilically attacks the aromatic ring (giving rise to an inverse H/D kinetic isotope effect of 0.8). These results have revealed a detailed experimental mechanistic picture of the oxidation reactions catalyzed by 1, based on direct characterization of the intermediates and products, and kinetic analysis of the individual reaction steps. Our detailed understanding of the mechanism of this reaction revealed both similarities and differences between synthetic and enzymatic aromatic hydroxylation reactions.; Thesis (Ph.D.)--Tufts University, 2011.; Submitted to the Dept. of Chemistry.; Advisor: Elena Rybak-Akimova.; Committee: Krishna Kumar, Charles Sykes, and Theodore Betley.; Keywords: Chemistry, and Inorganic Chemistry.